ANALYSIS SENTIMENT ON THE ACCEPTANCE OF CPNS 2021 ON TWITTER SOCIAL MEDIA USING TEXTBLOB - Widi Astuti (Jurnal Techno Nusa Mandiri, 2022)
The progress of information technology is growing rapidly along with the development of hardware and software developed by the world's largest companies. These advances have a significant impact on human life. Many jobs in human life use the help of technology. data mining technology, one of which is used in the field of research. In the process, data mining will extract valuable information by analyzing the existence of certain patterns or relationships from large data. Government agencies in Indonesia periodically organize the recruitment and selection of Candidates for Civil Servants (CPNS).